Análise da relação franqueador-franqueado em redes de franquias de alimentos. - Silva, André Gustavo Alves da (2005)
This dissertation investigates the organization architecture of franchise chains in Brazil, particularly in food franchising. We analyze the organizational architecture by means of a set of variables that allows to classify franchise chains in accordance with the typology of franchising generations, as it is usual in the franchising literature. In order to proceed with the analysis, this dissertation carried out an extensive survey with 223 Brazilian franchise chains and a qualitative research with six case-studies in food franchising. After a general description of the franchising system, the dissertation analyzes the organizational architecture of Brazilian franchise chains focusing on the following features: contractual mix, risk of brand name loss, upstream and downstream coordination. Based on these features, the dissertation describes the concept of franchising generations. In order to distinguish franchising generations, the following characteristics are investigated: number of company-owned and franchised units, experience in franchising, required standardization, consumer sensitivity to variation in product attributes, and governance structures in upstream and downstream transactions. By means of these variables, the dissertation classifies franchise chains into the two most relevant franchising models, the 3rd and 4th generations, i.e., Business Format Franchising and Learning Network Franchising. The empirical analysis indicates that the features of 3rd and 4th generation are sometimes present in the same chain, suggesting that there is a continuum between these two ideal models to organize a franchise chain.